(NsOBRANIE SO^INENIJ W DWENADCATI TOMAH(B:s (NpOWESTI I RASSKAZY (B/s (N~ASTX (B2s - (NtOLSTOJ(B, (NlEW nIKOLAEWI^s ((NmOSKWA(B:s (NpRAWDA(B,s, 1987)
(NwO WTOROJ TOM sOBRANIQ SO^INENIJ WO[LI POWESTI I RASSKAZY(B: "(NsEWASTOPOLX W DEKABRE MESQCE(B", "(NsEWASTOPOLX W MAE(B", "(NdWA GUSARA(B", "(NaLXBERT(B", "(NtRI SMERTI(B", "(NsEMEJNOE S^ASTXE(B", "(NpOLIKU[KA(B". (Na TAKVE IZ NEOKON^ENNOGO(B: "(NsWQTO^NAQ NO^X(B", "(NtIHON I mALANXQ(B", "(NdEKABRISTY(B" (NI DRUGOE(B.s
rus
Keywords: (NkLASSI^ESKAQ PROZAs; (NpOWESTI I RASSKAZYs